Analisis Pengaruh Kelengkapan Produk dan Promosi Penjualan Terhadap Keputusan Pembelian Konsumen di Transmart KarawanG - Winda Apriani; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The research was conducted at Transmart Karawang. In the current era of globalization, demand from consumers is increasing so as to provide profitable potential for the business world. A survey was conducted on the customer value index of 10 stores in Indonesia, one of the retail companies that is experiencing these problems is Transmart which occupies the fourth position. Reporting from kompas.com, it is said that at least 12 Transmart outlets will be permanently closed throughout 2022. The problem of declining sales levels at Transmart Karawang, as evidenced by the decreasing number of customers visiting the store, is the main subject of this study. This phenomenon is believed to arise due to consumer skepticism about their purchasing choices, which are influenced by product completeness and sales promotions. The purpose of this observation is to understand how product completeness and sales promotion affect consumer purchasing decisions at Transmart Karawang. Translated with DeepL.com (free version)The subjects of this research are consumers or customers of Transmart Karawang. The research methodology used quantitative and survey methodologies. The applied data sources include main data and supporting data, while the applied data collection techniques include questionnaires, face-to-face interactions, observations, and literature studies. A research sample of 99 respondents was selected from a population of 8422 using the Slovin formula. This research utilizes multiple linear regression analysis methodology using SPSS version 27.0 software to evaluate the effect of product completeness and sales promotion on purchasing decisions at Transmart Karawang. The research findings show that 82.9% of consumers in Transmart Karawang are influenced in their purchasing choices by the presence of product completeness and purchase promotions. A total of 17.1% of the evaluation was influenced by unresolved issues in this study.